IMPLEMENTATION OF THE ONLINE NEW STUDENT ADMISSION PROGRAM (PPDB) AT SMK NEGERI 4 TEBING TINGGI - Carinta Br Barus; Yanhar Jamaluddin; Beby Masitho Batubara (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the Implementation Of The Online New Student Admission Program (PPDB) At Smk Negeri 4 Tebing Tinggi is a national policy aimed at increasing transparency, accountability, and equal access to education. This study aims to analyze the implementation of the Online PPDB Program at SMK Negeri 4 Tebing Tinggi for the 2024/2025 Academic Year and to identify its supporting and inhibiting factors. This research uses a qualitative approach with a descriptive method. Data were collected through interviews, observation, and documentation. The policy implementation analysis uses the George Edward III model, which includes the aspects of communication, resources, disposition, and bureaucratic structure. The results show that the implementation of Online PPDB at SMK Negeri 4 Tebing Tinggi has generally been carried out in accordance with regulations and is quite effective in improving transparency and service efficiency. However, there are still obstacles in the form of limited digital literacy in the community, technical network disruptions, and an imbalance of interest in certain study programs. Therefore, although this policy has been implemented well, further improvements in socialization, strengthening of human resource capacity, and enhancement of supporting systems are still needed so that the objectives of Online PPDB can be optimally achieved.